Character Building Dalam Pembelajaran Multikultural: Suatu Alternatif Pembelajaran Membangun Budi Pekerti Manusia Indonesia - Ary Purwantiningsih (Prosiding Temu Ilmiah Nasional Guru, 2022)
This article discusses character building in multicultural learning and alternative learning to build Indonesian human character. The method used in analyzing this article is a literature study. Learning is needed to adapt to various cultures around the lives of students so that good behavior can carry out rights and obligations in society and can be developed through personal character development to anticipate and develop education that can shape the character of students and future generations. The beliefs, actions, and behavior of every human being in society, nation, and state are influenced by character, which has fundamental values ​​and meanings. This article discusses character building as an effort to build character, multicultural learning as global learning, and learning good manners Ato form Indonesian human character.